Integrating Disability, Transforming Feminist Theory - Garland-Thomson, Rosemarie (NWSA Journal, 2002)
This essay aims to amplify feminist theory by articulating and fostering feminist disability theory. It names feminist disability studies as an academic field of inquiry, describes work that is already underway, calls for needed study and sets an agenda for future work in feminist disability studies. Feminist disability theory augments the terms and confronts the limits of the ways we understand human diversity, the materiality of the body, multiculturalism, and the social formations that interpret bodily differences. The essay asserts that integrating disability as a category of analysis and a system of representation deepens, expands, and challenges feminist theory. To elaborate on these premises, the essay discusses four fundamental and interpenetrating domains of feminist theory: representation, the body, identity, and activism, suggesting some critical inquiries that considering disability can generate within these theoretical arenas.
Keywords: EDI; activisme; approches et analyses; corps; cours; discipline; militance; premier cycle; queer; ressource en ligne; santé; sciences humaines; sciences sociales; sex1920; thématiques; études critiques du handicap; études féministes

Standpoint theory, situated knowledge and the situated imagination - Stoetzler, Marcel; Yuval-Davis, Nira (Feminist Theory, 2002)
The aim of the article is to further assess and develop feminist standpoint theory by introducing the notion of the ‘situated imagination’ as constituting an important part of this theory as well as that of ‘situated knowledge’. The article argues that the faculty of the imagination constructs as well as transforms, challenges and supersedes both existing knowledge and social reality. However, like knowledge, it is crucial to theorize the imagination as situated, that is, as shaped and conditioned (although not determined) by social positioning.
Keywords: approches et analyses; cours; discipline; fem1000; justice sociale; militance; mouvements sociaux; point de vue situé; premier cycle; ressource en ligne; sciences humaines; thématiques; théories féministes; épistémologie